STUDENTS’ PERCEPTION IN ENGLISH ONLINE LEARNING DURING PANDEMIC AT SMK NEGERI 6 DUMAI - Shellika Safitri; Erni Erni; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research reviews students’ perceptions of English online learning in senior high school during pandemic Covid-19. The research was aimed to determine students’ perceptions of English online learning during the Covid-19 pandemic. The objective of the research is to get information about the students’ perceptions in online learning during pandemic especially in learning English at SMAN 5 Dumai. The Population of this research is the third - year students of SMAN 5 Dumai. The whole number of the population is about 227 students which consist of 7 classes. This study used cluster random sampling technique. Three of the classes is taken as the sample as many as 100 students. This research design used descriptive-quantitative method as the research data approach. There were 15 items in the questionnaire. The data was analyzed using a Likert-scale for the responses of questionnaire. The questionnaire were collected through Questionnaire Form. The findings showed that The findings of this study were revealed that there were differently according to the data questionnaire students selected previously, mostly stated contradictive perception negatively to the implementation of online learning. students considered normal to fosters students to create personal learning mode during pandemic situation which forces have limited interaction in classroom activities directly with teachers or classmates.Keywords: Perception, Online Learning